ON THE COMPLEX FORMULA OF THE APPARENT POWER IN CALCULATIONS OF THE ELECTRICAL SYSTEMS - Bаndia Baro (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper offers the mathematically correct notation of the coordinate axes on the plain of complex numbers for Theoretical Science of Electrical Engineering. The complexes of various electrical quantities (electromotances, voltages, currents, capacities, resistances, and conductivities) are proposed to notate similarly showing the significance of observing continuity and uniformity in notation. The author studies various forms of complex power notation. Of all forms of notation currently in use, he reasonably chooses the one mathematically proper and solely adequate to the physical processes. It is known that the calculation of the sine-wave current electrical circuits can be performed by way of transposing the sinusoidal equation (the trigonometrical method) which is cumbersome. Recomposing time diagrams (the timediagram method) of the required sinusoidal functions is demonstrative, however unveracious. The phasor-diagram method is convenient, more pictorial but, like any other graphical approach, moderately inaccurate, cumbersome especially for branched circuits. And finally symbolic (or complex) method which retains visual expressiveness of graphical solution since it is easy to build a phasor diagram by the symbolic notation of electrical quantities. The given method allows analytical solving issues with any degree of precision. Beyond that, the symbolic method holds consistency of the obtained results which follows from the inextricable link between different presentation-methods of the sine functions. There should be no contradictions between these methods which is the principle merit of the proposed notation form. And that will allow avoiding embarrassing mistakes.